ECO-CITY - Dreise, Lucas; Ledesma, Milton; Sovrano, Martín Enzo (My University, 2020)
My name is Milton Ledesma. I am 40 years old. I am Argentinian and I live in Paraná. I am an electromechanical engineer and I have a Master on Administration for Industries. I am the CEO of the company, I am in charge of taking the most important decisions, so I have a lot of consultors for this. I created this company with successful people, who are Lucas Dreise and Martín Sovrano. They are professionals and colleagues. We met at UTN, where we studied to become electromechanical engineers. Hello! My name is Lucas J. Dreise. I am 42 years old. Also, I am Argentinian, from Crespo and currently I live there. I am an electromechanical engineer and I hold a Doctorate in Structural Engineering with honors. My task in the Company is to give technical advice in the Department of Development and Execution. In this department we solve problems from a technical point of view. I am part of this company since it was created. Hi! I am Martín Sovrano. I am 39 years old. I am Argentinian and I live in Paraná. I have a degree in Electromechanical Engineering and a specialty in Environmental Engineering. I am in charge of the Purchasing and Sales Department; where we purchase materials and products that we need in the company and finally we sell them in the market. I can also contribute with design of new products. Eco-City is in the recycling and manufacturing business. We follow ecological standards for our products. We would like to address a problem of logistics in the Urquiza Park because we think that people need a better place to relax and spend their free time. Our company doesn’t have branches in the province. We have organized the presentation this way. First, we are going to develop our company description, where we are going to show our Markets and Services/Products that the Company offers. Then, we are going to talk about the company organization. After that we are going to tell you about to the company history
Keywords: Markets and Services; Mercados y Servicios; Fabricación de Productos Recreativos; Manufacture Products Recreational